Relationship between Motor and Nonmotor Symptoms and Quality of Life in Patients with Parkinson's Disease - Eduardo Candel-Parra; María Pilar Córcoles-Jiménez; Victoria Delicado-Useros; Antonio Hernández-Martínez; Milagros Molina-Alarcón (MDPI AG, 2021)
Background: Parkinson's disease (PD) is a chronic neurodegenerative disease that implies a progressive and invalidating functional organic disorder, which continues to evolve till the end of life and causes different mental and physical alterations that influence the quality of life of those affected. Objective: To determine the relationship between motor and nonmotor symptoms and the quality of life of persons with PD. Methods: An analytic, descriptive, cross-sectional study was conducted with patients with different degrees of PD in the Albacete Health district. The estimated sample size required was 155 patients. The instruments used for data collection included a purpose-designed questionnaire and "Parkinson's Disease Questionnaire" (PDQ-39), which measures eight dimensions and has a global index where a higher score indicates a worse quality of life. A descriptive and bivariate analysis was conducted (SPSS® IBM 24.0). Ethical aspects: informed consent and anonymized data. Results: A strong correlation was found between the number of motor and nonmotor symptoms and global health-related quality of life and the domains mobility, activities of daily living, emotional well-being, cognitive status, and pain (p < 0.05). Receiving pharmacological treatment and taking more than four medicines per day was significantly associated with a worse quality of life (p < 0.05). Patients who had undergone surgical treatment did not show better global quality of life (p = 0.076). Conclusions: All nonmotor symptoms and polypharmacy were significantly associated with a worse global quality of life.